FEASIBILITY STUDY OF THE HIGH-YIELDING HORTICULTURE SEEDS BREEDING AGRIBUSINESS DEVELOPMENT IN EAST JAVA - Dwi Retnonigsih (Socio-Economics/Agribusiness Department, 2017)
Horticulture is one of important subsectors for agricultural development in East Java. Increasing demand of high quality seed of horticulture results an increasing demand of land for seed breeding. The objectives of this research were to analyze potential of various potential horticultural crops, to calculate economic feasibility, to analyze business marketing chain and to identify potential horticultural seeds breeding for agribusiness development. Data analysis method that used in this research was Location Quotient (LQ), Supply Chain, Business Feasibility (Feasibility Study), and AHP (Analytical Hierarchy Process). The research was conducted in 5 (five) Regencies. The research conducted by interview to the breeder, user farmers, and seeds seller. The research results showed that potential horticultural seeds in five Regencies based on LQ and local government program are rose apple (Syzygium aqueum), longan fruit, durian, ginger, bird’s eye chili or thai chili, orange, potato, and mango. All potential commodities above were feasible to be developed based on R/C ratio, B/C ratio, NPV, and IRR calculation. Marketing chain for those potential commodities vary started from breeder farmer, middleman, farmer group, Regional Owned Enterprises to the user farmer or individual farmer. The prospect of those potential horticultural seeds breeding based on AHP analysis results some attributes to be considered, they are seeds quality and growth capability.